Nanofabrication of superhydrophobic fluidic concentrators coupled with metallic plasmonic nano-antennas for SERS analysis in the sub-femtomolar range - Sofien Ramos; Victor Fabre; Mathieu Arribat; Aurélie Lecestre; Adrian Laborde; Frank Carcenac; Philippe Louarn; Emmanuelle Trevisiol; Christophe Vieu (Micro and Nano Engineering)
Self-assembled silicon nanopillars decorated with metallic nanoparticles have emerged as efficient Surface Enhanced Raman Spectroscopy (SERS) substrates. In this study, we combine black Silicon Reactive Ion Etching-Inductively Coupled Plasma (RIE-ICP) and thin film deposition of Silver (Ag) to produce this type of surface equipped with plasmonic nano-antennas. The paper describes a quantitative methodology for optimizing the fabrication process of such silicon SERS supports and specifically the determination of the nominal thickness of the Ag thin film, that upon fragmentation at the surface of the black‑silicon nanopillars, forms Ag nanoparticles capable of enhancing the local electromagnetic field. This parameter is crucial for tuning the surface density of generated hot spots on the surface and their electromagnetic enhancement factors. We propose a methodology based on the generation of hierarchical superhydrophobic fluidic concentrators and the development of a home-made algorithm for analyzing SERS spectra of Rhodamine B (RhB) solution at sub-femtomolar concentrations. The developed hierarchical clustering algorithm automatically selects from all the spectra acquired on the region of interest, the surface enhanced spectra containing at least three vibrational Raman signatures of RhB. The objective criterion for optimizing the fabrication process or for evaluating the performance of any SERS substrate is then simply the total number of RhB spectra finally retained by the algorithm. We detail the fabrication processes, the algorithmic method and through its experimental implementation we show how to tune the parameters of the algorithm for selecting the optimal Ag thin-film thickness.